Resource Constraints and the Right of the Mental Disorders to Receive Appropriate Treatment - Wallach, Sacha (Victoria University of Wellington Law Review, 2000)
This article explores the right of mentally disordered patients to appropriate treatment after the Mental Health (Compulsory Assessment and Treatment) Act 1992. It then examines the detrimental impact of resource constraints on this right, especially the undermining of the presumption in favour of community treatment. It concludes that resource constraints are not an appropriate justification for denial of the right to appropriate treatment.